Tectonic setting of Ni-Cu-PGE deposits in the central part of the Cape Smith Belt - Giovenazzo, D.; Picard, C.; Guha, J. (Geoscience Canada, 1989)
Summary The Ni-Cu-PGE sulphide deposits in the central and eastern parts of the Cape Smith Belt are best developed near the contactbetween the Povungnituk and Chukotat Groups The deposits are associated with differentiated sills and ultramafic intrusions forming part of the feeder system to the lower Chukotat Group which comprises alternating olivine and pyroxene-phyricbasalts. The intrusions were emplaced near or at the axis of an oceanic proto-rift. The sulphide deposits are concentrated in two east-west trending horizons: (1) the Raglan horizon, containing deposits associated with sub-volcanic ultramafic intrusions {e.g., Lac Cross, Katinik and Donaldson sulphide deposits) and (2) the Delta horizon which contains deposits associated with differentiated sills (e.g., Delta region) and ultramafic intrusions (Méquillon dyke, Bravo Sills).